S. Rebecca Martin. The Art of Contact. Comparative Approaches to Greek and Phoenician Art. - Donnellan, Lieve (Journal of Greek Archaeology, 2019)
Two cartoons in a much-cited handbook on archaeological theory depict the practitioners of the discipline in 1988 and again, in 1998. The first cartoon on the discipline in 1988, shows a ferocious fight going on between representatives of different theoretical approaches. Situated at the periphery are, on the side, confused members of the public, and, on the other side, turned with his back to the rest of the world, a bearded pipe-smoking Classical Archaeologist, browsing a ‘monumental’ publication while seated on another pile of Classical Archaeology books. The next cartoon shows the discipline ten years later, in 1998. The fight at the core has dissolved and made place for stimulating parallel debates between factions in which members of the public participate. Untroubled and still seated on his pile of books, is the same bearded pipe-smoking Classical Archaeologist.